Stress-strain model for partial CFRP confined concrete - Ferreira, Débora R. S. M. (2008)
Concrete columns requiring strengthening intervention always contain a certain percentage of steel hoops. Applying strips of wet lay-up carbon fiber reinforced polymer (CFRP) sheets in-between the existent steel hoops might, therefore, be an appropriate confinement technique with both technical and economic advantages, when full wrapping of a concrete column is taken as a basis of comparison. To assess the effectiveness of the partial wrapping technique, circular cross section concrete columns were confined by distinct CFRP arrangements and tested under direct compression. The experimental program was designed to evaluate the influence of the concrete strength class, the stiffness of the wet lay-up CFRP sheet, the distance between strips, the width of the strip, and the number of layers per each strip. The Harajli et al. model was modified in order to predict the compression stress-strain behaviour of reinforced concrete column elements partially and totally confined by CFRP lay-up sheets. The main results of the experimental program are hereby presented and analysed. The model’s performance is assessed using the experimental results.